Football of ethics: COVID-19 and the football community`s response - Crang, L. (The Football Collective, 2020)
Having discussed the possible changing nature of football in a previous post, with Christoph, I was interested in how the football community has reacted to this pandemic so far. This follow up is to look at just that.